Gynacantha subinterrupta Rambur, 1842: an addition to the odonates (Insecta: Odonata: Aeshnidae) of Bangladesh - M. Kawsar Khan (Journal of Threatened Taxa, 2015)
Gynacantha subinterrupta Rambu 1842 is first time recorded from Bangladesh. The species is described from two male specimens collected from Tilagor Eco Park, Sylhet.  Description, identification keys and distribution range of the species is provided.